Profitability, energetics and GHGs emission estimation from rice-based cropping systems in the coastal saline zone of West Bengal, India - Ray, Krishnendu; Sen, Piyali; Goswami, Rupak; Sarkar, Sukamal; Brahmachari, Koushik; Ghosh, Argha; Nanda, Manoj Kumar; Mainuddin, Mohammed (PloS one, 2020)
This study compares thirteen rice-based cropping systems in the coastal part of West Bengal, India in terms of productivity, profitability, energetics, and emissions. Information on the crop management practices of these systems was collected on 60 farms through a questionnaire survey. Rice-bitter gourd system was observed to have the highest system yield (49.88 ± 4.34 tha-1yr-1) followed by rice-potato-ridge gourd (37.78 ± 2.77 tha-1yr-1) and rice-potato-pumpkin (36.84 ± 2.04 tha-1yr-1) systems. The rice-bitter gourd system also recorded the highest benefit:cost ratio (3.92 ± 0.061). The lowest system yield and economics were recorded in the rice-fallow-fallow system. Rice-sunflower system recorded highest specific energy (2.54 ± 0.102 MJkg-1), followed by rice-rice (2.14 ± 0.174 MJkg-1) and rice-fallow-fallow (1.91 ± 0.327 MJkg-1) systems, lowest being observed in the rice-bitter gourd (0.52 ± 0.290 MJkg-1) and rice-pointed gourd (0.52 ± 0.373 MJkg-1) systems. Yield-scaled GHGs (YSGHG) emission was highest (1.265 ± 0.29 t CO2eqt-1 system yield) for rice-fallow-fallow system and was lowest for rice-vegetable systems. To estimate the uncertainty of the YSGHG across different systems under study, Monte-Carlo Simulation was performed. It was observed that there was a 5% probability of recording YSGHG emission > 1.15 t CO2eqt-1 system yield from different cropping systems in the present experiment. Multiple system properties such as productivity, economics, energy, and emission from all rice-based systems taken together, the rice-vegetable system performed consistently well across parameters and may be practised for higher economic returns with judicious and sustainable utilization of resources in the coastal saline tracts of the region.